Quality of Life and cost of living in colon cancer patients - Kouris, Ioannis; Kalogianni, Antonia; Kapadochos, Theodoros; Kiranoudi, Aggeliki; Pavlatou, Niki; Kyriakopoulos, Antonios; Toylia, Georgia (Health & Research Journal, 2025)
Introduction: Colon cancer is a common form of cancer. The main goal of any therapeutic approach is the patient’s best quality of life combined with the effectiveness of the treatment. Aim: To explore the quality of life of patients with colon cancer in Greece as well as to estimate the change in their cost of living. Material and methods: This is a prospective descriptive observational study, conducted during the period January 2020- January 2022. In total, 192 participants were enrolled in the study. Data collection was performed by using a questionnaire both open-ended and closed-ended questions (demographic, socioeconomic and lifestyle characteristics, questions for the assessment of the changes in patients’ financial cost of living and their quality of life). Data analysis was performed using SPSS ver. 21.0 (Statistical Package for Social Sciences). Results: The mean age of the patients was 66.7 years, while 39.6% were women. The majority of patients (73.4%) were retired and 14.6% were employed. The average cost of living of the patients due to the disease during the previous semester was €3.714. Scores on the mental and physical health summary scales were significantly lower than 50 indicating that patients’ quality of life was significantly worse than average in both mental and physical health. Younger patients had better general health, p=0.047. Conclusion: Τhe generally reduced quality of life for patients with colon cancer, can be interpreted in relation to the increased anxiety of patients, pain, as well as the significant financial burden they face.